Estimation Of Carbon Footprint Emission Consumption In Electricity From Individual Student: Case Study In Department Of Economics, Universitas Diponegoro - Mentari Anggun Djatayu; Indah Susilowati; Aini Nur Furoida; Cici Musliha (School of Postgraduate Studies, Diponegoro Univer, 2025)
This research aims to analyze estimated carbon footprint emissions based on daily electricity consumption, as well as provide strategies aimed at reducing greenhouse gas emissions. The method applies a quantitative approach using descriptive statistics. Data collection was obtained through purposive sampling of economics students at Diponegoro University, with a total sample of 61 students. The CO₂ emissions calculates by multiplying electricity use with the ESDM emission factor based on the 2006 IPCC Guidelines. The result shows that the estimated carbon footprint per category, which presents a comparison of the consumption of electronic goods among upper middle class and lower middle-class students, there are 3 categories: low, medium and high where cross tabulation obtained results in the low category of 93 percent out of a total of 100 percent. Therefore, the students who consume electricity resulting in carbon emissions at Diponegoro University are relatively low, reaching 93 percent and the highest consumption reaches 4.92 percent, which is still below 5 percent of the carbon consumption standard, which is a good achievement in helping to maintain the sustainability of the university's environment.